2017
DOI: 10.1016/j.ajhg.2017.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunction of the Cerebral Glucose Transporter SLC45A1 in Individuals with Intellectual Disability and Epilepsy

Abstract: Glucose transport across the blood brain barrier and into neural cells is critical for normal cerebral physiologic function. Dysfunction of the cerebral glucose transporter GLUT1 (encoded by SLC2A1) is known to result in epilepsy, intellectual disability (ID), and movement disorder. Using whole-exome sequencing, we identified rare homozygous missense variants (c.526C>T [p.Arg176Trp] and c.629C>T [p.Ala210Val]) in SLC45A1, encoding another cerebral glucose transporter, in two consanguineous multiplex families w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 16 publications
1
22
0
Order By: Relevance
“…It is a protein-coding gene and associated with intellectual developmental disorder with neuropsychiatric features and autosomal recessive non-syndromic intellectual disability ( https://www.genecards.org/cgi-bin/carddisp.pl?gene=SLC45A1 ). Srour et al ( 2017 ) studied homozygous missense variants in SLC45A1 on four affected children from two unrelated consanguineous families with moderate to severe intellectual disability associated with epilepsy and variable neuropsychiatric features. They concluded that autosomal-recessive mutations in SLC45A1 result in intellectual disability, movement disorder, and epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…It is a protein-coding gene and associated with intellectual developmental disorder with neuropsychiatric features and autosomal recessive non-syndromic intellectual disability ( https://www.genecards.org/cgi-bin/carddisp.pl?gene=SLC45A1 ). Srour et al ( 2017 ) studied homozygous missense variants in SLC45A1 on four affected children from two unrelated consanguineous families with moderate to severe intellectual disability associated with epilepsy and variable neuropsychiatric features. They concluded that autosomal-recessive mutations in SLC45A1 result in intellectual disability, movement disorder, and epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the potential treatment target, there is some promising indication for ketogenic diet in individuals with SLC45A1 mutations, however, further investigation is needed [ 49 ].…”
Section: Common Pathogenic Variants In Glut-1 Deficiencymentioning
confidence: 99%
“…There are four members of the SLC45 family, including SLC45A1, SLC45A2, SLC45A3, and SLC45A4. SLC45A1 is mainly expressed in the brain, especially on the ventral surface of the medulla oblongata [ 4 ]. The expression of SLC45A1 is increased at low oxygen concentration or pH [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…SLC45A1 is mainly expressed in the brain, especially on the ventral surface of the medulla oblongata [ 4 ]. The expression of SLC45A1 is increased at low oxygen concentration or pH [ 4 ]. It is speculated that it may be involved in glucose transport and H+ ion regulation [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation